Importance of rheological properties in enrobing efficiency of dark chocolate: application in wafer products - Ertural, Goksen Isik; Gunes, Recep; Toker, Omer Said; Palabiyik, Ibrahim; Konar, Nevzat; Sagdic, Osman (WILEY, 2023)
In this study, the rheological properties of dark chocolate used for enrobing in wafer production were modified with the use of lecithin and polyglycerol polyricinoleate (PGPR), and its effects on the final product were investigated. Lecithin was added to the dark chocolate from 0.1 to 0.8 g per 100 g in increments of 0.1 g, then, 0.10, 0.15, and 0.20 g per 100 g PGPR were combined separately with 0.40 g per 100 g lecithin containing sample. There were significant differences in the enrobing ratios, colour, texture, and sensory parameters of the wafer samples (P < 0.05) enrobed with dark chocolate, in which lecithin and PGPR were used together, due to the changes in the flow behaviour of the chocolate. The wafers enrobed with emulsifier-free dark chocolate had the highest enrobing ratio (72.3%), while it was 45% in the sample enrobed with dark chocolate containing 0.40 g per 100 g lecithin + 0.20 g per 100 g PGPR. In parallel with the decrease in the enrobing ratio, changes occurred in the textural hardness and fracturability values of the samples. On the other hand, as the enrobing ratio decreased, the structure of the wafer sheets became more prominent during consumption, resulting in an increase in the sensory evaluation scores.
Keywords: Chocolate; enrobing; food additive; rheology; wafers; TEMPERATURE; EMULSIFIER; Food Science & Technology